1989
DOI: 10.1007/bf00412971
|View full text |Cite
|
Sign up to set email alerts
|

Soluble II-2 receptor serum levels ? a marker for disease progression in patients with HIV-1 infection

Abstract: Serum levels of soluble Il-2 receptors (sIl-2R) were measured in 88 patients with HIV infection, 28 patients from high-risk groups, and 28 normal donors. Elevated sIl-2R levels were found in 46% of asymptomatic seropositive patients, in 68% of patients with persistent generalized lymphadenopathy, and in 81% of patients with AIDS. Mean sIl-2R values increased with the progression of the disease and were most pronounced in patients with AIDS. A close correlation was found between sIl-2R levels and beta2-microglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Mean sIL-2R values increased with the progression of the disease and were most pronounced in patients with AIDS. They established that sIL-2R is a valuable parameter in monitoring the course of the HIV infection [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Mean sIL-2R values increased with the progression of the disease and were most pronounced in patients with AIDS. They established that sIL-2R is a valuable parameter in monitoring the course of the HIV infection [16]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study on Jaagsiekte retrovirus (JSRV) found that although the soluble form of its receptor, Hyal2 (sHyal2), did not mediate the entrance of a JSRV-pseudotype retroviral vector into cells lacking the integrated Hyal2, this purified soluble protein significantly inhibited the infection of the pseudotyped vector in the target cells of JSRV [13] . Moreover, some soluble receptors in the plasma can be considered markers of disease progression, such as soluble TNF receptor (sTNFR) II and soluble IL-2 and IL-6 receptors in HIV-1-infected patients [10] , [14] , [32] . Therefore, soluble receptors play important roles in the interactions between viruses and hosts [33] [37] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study on Jaagsiekte retrovirus (JSRV) found that although the soluble form of its receptor, Hyal2 (sHyal2), did not mediate the entrance of a JSRV-pseudotype retroviral vector into cells lacking the integrated Hyal2, this purified soluble protein significantly inhibited the infection of the pseudotyped vector in the target cells of JSRV [13]. Moreover, some soluble receptors in the plasma can be considered markers of disease progression, such as soluble TNF receptor (sTNFR) II and soluble IL-2 and IL-6 receptors in HIV-1-infected patients [10,14,32]. Therefore, soluble receptors play important roles in the interactions between viruses and hosts [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%